Formation of novel rice-like intermetallic phases and changes in the mechanical, microstructural and electrical properties of Sn–5Sb alloys with addition Ag and Bi - Karaköse, Ercan; Kılıçaslan, M. Fatih; Çolak, Hakan (Elsevier BV, 2016)
Abstract In the present study, the effects of Ag and Bi additions (1 wt.%) on the microstructural, thermal, mechanical and electrical properties of Sn–5Sb solder alloys were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), microhardness tests, and four probe measurements. It was observed that the melting point of Sn–5Sb solder alloy decreased with the addition of Ag and Bi. It was found that the final microstructure of rapidly solidified Sn–5Sb-1X (X = Ag and Bi) alloys was strictly dependent upon the wheel speeds; the microstructures changed from a coarse dendritic and needle-like structure to a refined ultra fine dendritic and rice-like structure with increasing wheel speed. Cooling rate was also effective on both the mechanical and electrical properties. It was found that all of the alloys exhibit higher mechanical properties with increasing cooling rate and/or decreasing testing temperature. Similarly, significant improvements of 32% and 9% in electrical conductivity of both of the alloys were obtained with the addition of Ag and Bi, respectively. The microstructural evolution of the Sn–5Sb based alloys plays a crucial role in influencing the mechanical properties of these alloys.